Rehabilitation Programs of Executive Functions in Young and Middle Adulthood based on Computational Systems: a Scoping Review. - Robledo-Castro, Carolina; Lerma Castaño, Piedad Rocío; Pachón Ospina, Luis Gerardo (Revista de Investigación e Innovación en Ciencias de la Salud (RIICS), 2023)
Introduction. The use of computational systems has ventured into different healthcare areas, such as rehabilitation and stimulation of cognitive processes. To this date, it is possible to identify some reviews collecting studies on the efficacy and effects of those programs in groups such as older adults, children, and teenagers; there is a lack of academic literature giving an account of young and middle-aged adults. Objective. To identify empirical studies that measured the feasibility and effect of computer-based stimulation and rehabilitation programs for cognitive functions in young and middle-aged adults. Materials and methods. The PRISMA ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) extension was used as a base for a scoping review, as suggested by Cochrane Collaboration. Five databases --Science Direct, Scopus, Springer, PubMed, and Taylor & Francis-- were used to trace information. The data registry and synthesis of the results was carried out independently by two reviewers. Results. 896 registries were found between 2015 and 2022, of which 91 met the eligibility principles, which evaluated the effects of programs based on computational systems on executive functions on young and middle-aged adults. Conclusion. Most of the interventions based on computational systems showed to be feasible and had moderate to significant effects on executive functions in young and middle-aged adults.